A Scale to Measure Attitude of Dairy Personnel towards the Organizational Processes of COMPFED - Singh, S. R. K.; Chand, Ram; Gautam, U.S.; Singh, D.K. (Indian Journal of Extension Education, 2010)
The attitude of the dairy personnel forms an essential component for effectiveness of the organization. Keeping in view the importance of attitude, this study was designed to construct a standardized attitude scale to measure the attitude of the dairy personnel towards organizational processes of COMPFED. An attitude scale was developed using Summated Rating Technique. Total 90 statements were selected after the scrutiny of the panel of judges. Later only 40 statements were selected which had relevancy percentage, relevancy weightages and mean relevancy score of 70.0, 0.72 and 3.20, respectively. Finally 19 statements which had ‘t’ value 1.80 and above were qualified for inclusion in the scale.